ANALISIS PERANGKAT PEMBELAJARAN IPA TERPADU BERBASIS DARING YANG DIGUNAKAN OLEH GURU SMP NEGERI PONTIANAK - Arisatul Fahmi; Stepanus Sahala Sitompul (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2022)
The research was carried out with the aim of analyzing online learning tools during the Covid-19 pandemic. The tools analyzed are: (1) learning implementation plans (RPP), (2) teaching materials, (3) student worksheets (LKPD) and (4) learning outcomes used by junior high school teachers (SMP) in terms of aspects preparation, process and results. The specific objectives to be achieved through this research are to: (1) describe the results of the RPP analysis in terms of the derivatives of the Minister of Education and Culture of the Republic of Indonesia issuing circular letter number 4 of 2020 concerning the implementation of education policies in the emergency period of the spread of covid-19, (2) describe the results of the analysis of teaching materials in terms of making online teaching materials used for the learning process, (3) describing the results of the LKPD analysis in terms of the development of the assessment process, character and activity as demanded in the 2013 curriculum, and (4) knowing learning outcomes in terms of daily tests learners. This research includes evaluation research. The instruments used are questionnaires, document recording, and interviews. Learning devices were collected using cluster sampling technique, namely grouping by school. There are 6 schools that are used as research subjects. So the total sample size is: 6 teachers, 6 lesson plans, 6 teaching materials, 6 LKPD, and 6 learning outcomes in the form of daily test scores. The data analysis technique used is descriptive qualitative analysis technique and descriptive statistical analysis. The results showed that: the preparation and process carried out by the teacher in making learning tools were very good. Based on the results of the analysis, the lesson plans produced by the teachers are in the good category, the teaching materials are in the good category, the LKPD is in the less category and learning outcomes have increased during online learning.